Composite separator and preparation method and application thereof

CN122918641APending Publication Date: 2026-10-16WUXI LONGI HYDROGEN TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510425455.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0004]相关技术中,隔膜用于阻隔氢气和氧气相互混合,则要厚度较厚;而隔膜较厚时,电解液中的离子较难通过,较难兼顾形成较好的气体阻隔效果以及较好的离子透过率

Benefits of technology

[0009] According to embodiments of this application, by using a first polymer and a second polymer having the same main chain, the dense layer and the porous layer are more tightly bonded, which helps to improve the mechanical strength and thermal stability of the composite separator, making it more stable during battery charging and discharging and extending the service life of the composite separator. The introduction of the porous layer increases the ion conductivity of the composite separator, while the introduction of the dense layer helps to prevent the mixing of gases on both sides of the composite separator. Through the synergistic arrangement of the porous layer and the dense layer, both good gas barrier effect and good ion permeability can be achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918641A_ABST
    Figure CN122918641A_ABST
Patent Text Reader

Abstract

The application provides a composite diaphragm and a preparation method and application thereof, and belongs to the technical field of diaphragms. The composite diaphragm comprises a porous layer and two dense layers, the two dense layers are respectively located on the opposite two surfaces of the porous layer; the material of the porous layer is a first polymer with a first functional group, the material of the dense layer is a second polymer with a second functional group; the first polymer and the second polymer have the same main chain; the first functional group and the second functional group are ionic groups with the same polarity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of diaphragm technology, specifically to a composite diaphragm, its preparation method, and its application. Background Technology

[0002] Alkaline water electrolysis is a sustainable and green method for producing hydrogen. It produces hydrogen with high purity and, compared to traditional methods, does not require the use of precious metal catalysts, which helps reduce costs.

[0003] An alkaline water electrolysis electrolyzer for hydrogen production mainly consists of a water splitting electrode and a diaphragm. During the water electrolysis process, oxygen is generated at the anode electrode and hydrogen is generated at the cathode electrode. The diaphragm's function is to prevent hydrogen and oxygen from mixing, thus ensuring the purity of the hydrogen. Simultaneously, the diaphragm must allow ions in the electrolyte to pass through, ensuring the continuous operation of the electrolysis process.

[0004] In related technologies, the membrane is used to prevent hydrogen and oxygen from mixing, so it needs to be relatively thick. However, when the membrane is thick, it is more difficult for ions in the electrolyte to pass through, making it difficult to achieve both good gas barrier effect and good ion permeability. Summary of the Invention

[0005] In view of this, in order to at least partially solve the aforementioned technical problems, this application provides a composite diaphragm, its preparation method, and its application.

[0006] According to one embodiment of this application, a composite membrane is provided, comprising a porous layer and two dense layers, the two dense layers being located on opposite surfaces of the porous layer; the porous layer is made of a first polymer having a first functional group, and the dense layers are made of a second polymer having a second functional group; the first polymer and the second polymer have the same main chain; the first functional group and the second functional group are ionic groups having the same polarity.

[0007] According to another embodiment of this application, a method for preparing a composite separator is provided, comprising: coating a first casting solution onto a first substrate and forming pores to obtain a porous base membrane; coating a second casting solution onto a second substrate and partially drying it to obtain an adhesive coating; covering the porous base membrane onto the adhesive coating and drying it to obtain a porous layer with a uniform dense layer on its surface; covering the surface of the porous layer with a uniform dense layer away from the dense layer onto another adhesive coating and drying it to obtain a composite separator; wherein the first casting solution is a first polymer solution having a first functional group; the second casting solution is a second polymer solution having a second functional group; the first polymer and the second polymer have the same main chain; and the first functional group and the second functional group are ionic groups with the same polarity.

[0008] According to another embodiment of this application, a composite membrane as described above is provided for use in alkaline water electrolysis for hydrogen production, fuel cells, flow batteries, and seawater desalination.

[0009] According to embodiments of this application, by using a first polymer and a second polymer having the same main chain, the dense layer and the porous layer are more tightly bonded, which helps to improve the mechanical strength and thermal stability of the composite separator, making it more stable during battery charging and discharging and extending the service life of the composite separator. The introduction of the porous layer increases the ion conductivity of the composite separator, while the introduction of the dense layer helps to prevent the mixing of gases on both sides of the composite separator. Through the synergistic arrangement of the porous layer and the dense layer, both good gas barrier effect and good ion permeability can be achieved. Attached Figure Description

[0010] The above and other objects, features and advantages of this application will become clearer from the following description of embodiments with reference to the accompanying drawings, in which:

[0011] Figure 1 A schematic diagram of the cross-section of the composite diaphragm according to an embodiment of this application is shown;

[0012] Figure 2 A flowchart illustrating the preparation method of the composite separator according to an embodiment of this application is shown;

[0013] Figure 3 A diagram illustrating the preparation process of a composite membrane according to an embodiment of this application is shown. Detailed Implementation

[0014] The embodiments of this application will now be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of this application. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of this application for ease of explanation. However, it will be apparent that one or more embodiments may be implemented without these specific details. Furthermore, descriptions of well-known structures and technologies are omitted in the following description to avoid unnecessarily obscuring the concepts of this application.

[0015] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of this application. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.

[0016] When using expressions such as "at least one of A, B, and C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, and C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.). When using expressions such as "at least one of A, B, or C," the expression should generally be interpreted in accordance with the meaning commonly understood by a person skilled in the art (e.g., "a system having at least one of A, B, or C" should include, but is not limited to, systems having A alone, having B alone, having C alone, having A and B, having A and C, having B and C, and / or having A, B, and C, etc.).

[0017] In this application, "anion exchange membrane" refers to a type of polymer membrane containing basic active groups that selectively permeates to anions; it is also called an ion-selective permeable membrane. An anion exchange membrane consists of three parts: a polymer backbone with fixed groups (also called a polymer matrix or base membrane), positively charged active groups (i.e., cationic active groups), and freely movable anions (such as OH-) on the active groups. - ).

[0018] In this application, "cation exchange membrane" refers to a type of polymer membrane that selectively permeates cations. A cation exchange membrane consists of three parts: a polymer backbone with fixed groups (also called a polymer matrix or base membrane), negatively charged active groups (i.e., anionic active groups), and freely movable cations (such as H+) on the active groups. + ).

[0019] In the process of producing hydrogen through water electrolysis, hydrogen and oxygen are typically produced separately from the cathode and anode with relatively low energy consumption. A diaphragm is placed between the cathode and anode to prevent the two gases from mixing, ensuring the purity of the hydrogen while retaining ion transport capabilities. This creates a current loop in the electrolysis process, thus guaranteeing the stability and continuity of the electrolyzer. During the use of the electrolyzer, the diaphragm also needs to possess good mechanical strength to withstand the impact of the electrolyte and generated gases over extended periods.

[0020] It is understandable that anion exchange membranes can effectively conduct hydroxide ions in an alkaline environment, thereby promoting the electrolysis of water. Compared with traditional proton exchange membranes, anion exchange membranes are less expensive and have better durability and stability, and are widely used in hydrogen production through water electrolysis.

[0021] Specifically, anion exchange membranes utilize their internal conduction channels to transfer hydroxide ions from the cathode to the anode, thereby achieving water electrolysis.

[0022] In related technologies, a composite membrane is formed by using a base membrane and a polyelectrolyte coated on it. However, the poor compatibility between the base membrane and the polyelectrolyte leads to delamination and membrane peeling during use, which affects the ion conduction effect of the composite membrane structure and may also cause gas permeation.

[0023] In realizing the concept of this application, it was discovered that by forming a structure with a dense layer sandwiched between porous layers, the porous layers can provide better ion conduction. When applied in an electrolytic cell, this creates a current loop during electrolysis, thereby ensuring the stability and continuity of the electrolytic cell. Simultaneously, the dense layer effectively isolates the electrolyzer from gases. Furthermore, using a polymer material with the same main chain as the membrane material results in a tighter bond between the porous and dense layers.

[0024] Specifically, according to one embodiment of this application, a composite diaphragm is provided. Figure 1 A schematic diagram of the cross-section of the composite diaphragm according to an embodiment of this application is shown, as follows: Figure 1 As shown, it includes a porous layer and two dense layers, with the two dense layers located on opposite surfaces of the porous layer. The porous layer is made of a first polymer having a first functional group, and the dense layers are made of a second polymer having a second functional group; the first polymer and the second polymer have the same main chain; the first functional group and the second functional group are ionic groups with the same polarity.

[0025] It is understood that the porous layer, with its tiny pores, facilitates ion transport and provides good ion permeability for the composite membrane. The dense layer, compared to the porous layer, has a more compact structure, contributing to effective gas barrier properties. The two dense layers are located on either side of the porous layer, preventing gas from mixing into the porous layer and affecting ion permeability. This application, by combining the porous layer with two dense layers, achieves a composite membrane that possesses both high ion conduction efficiency and good gas barrier performance.

[0026] Furthermore, this application uses a first polymer with the same main chain structure as the material of the porous layer and a second polymer with the same main chain structure as the material of the dense layer. This results in a tighter bond between the porous and dense layers, good compatibility among the three layers, and the absence of obvious phase interfaces or boundaries between the porous layer and each dense layer. This avoids the problems of membrane delamination or poor compatibility that may occur during use in related technologies, further improving the bonding strength between the porous and dense layers, thereby enhancing the mechanical strength of the composite membrane and providing a more effective ion transport effect. In subsequent applications, the composite membrane exhibits good stability and can be used in long-term cycles.

[0027] Since the first and second functional groups are ionic groups with the same polarity, it can be understood that, for example, both the first and second functional groups can be positively charged ionic groups. In this case, the composite membrane is a polymer membrane with positively charged ionic groups fixed on it, which is an anion exchange membrane. At this time, the positively charged ionic groups can have freely moving anions (such as OH-). - This enables the transport of anions.

[0028] Alternatively, both the first and second functional groups in this application can be negatively charged ionic groups. In this case, the composite membrane is a polymer membrane with fixed negatively charged ionic groups, i.e., a cation exchange membrane. The negatively charged ionic groups can then have freely moving cations (such as H+). + This enables the transport of cations.

[0029] In some embodiments, the porous layer has multiple pore structures, at least some of which are independent of each other, thereby making the distribution of pore structures more uniform. This allows full utilization of the structural characteristics of the porous layer to achieve uniform ion transport, thereby improving ion transport efficiency.

[0030] In some embodiments, the porosity of the porous layer is 5-23%, for example, 5%, 8%, 10%, 13%, 15%, 18%, 20%, or 23%. This configuration ensures good ion transport efficiency while allowing the formed porous layer to form a membrane structure with good mechanical strength. When the porosity of the porous layer is less than 5%, the improvement in ion transport efficiency is poor; when the porosity is greater than 23%, it is difficult to form the porous layer and to prepare a layered structure with sufficient supporting strength. Even if a layered structure with a certain shape is prepared, excessive swelling may occur during subsequent use in the electrolyte, leading to damage and making long-term cyclic use difficult.

[0031] Optionally, the porosity of the porous layer is 8 to 12%, for example, it can be 8%, 9%, 10%, 11% or 12%, etc. This setting can take into account the ion transport efficiency of the composite membrane while having good support performance.

[0032] The pore structure has a length dimension of 0.1–0.8 μm in the porous layer, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or 0.8 μm. The pore structure also has a width dimension of 0.1–0.8 μm in the porous layer, for example, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, or 0.8 μm. This configuration allows the pore structure to provide good ion exchange while avoiding the pitting or uneven / uneven ion transport that can occur with excessively large pores.

[0033] Please refer to Figure 1 In terms of distribution, the pore structure can be understood as two pore structures not overlapping, or two pore structures overlapping to form one large pore structure, which is then calculated as one pore structure.

[0034] Optionally, the pore structure has a length dimension of 0.4~0.6 μm and a width dimension of 0.4~0.6 μm in the porous layer. This configuration ensures both good ion conduction and improved mechanical strength of the porous layer, contributing to better stability and extending the service life of the composite membrane.

[0035] In some embodiments, the porosity of the dense layer is less than 3%, for example, it can be 0, 1%, 2%, or 2.5%, and at least one of the two dense layers has a porosity of 0. This configuration can further reduce gas mixing on both sides of the composite membrane, which helps to improve the purity of hydrogen when applied in the field of water electrolysis for hydrogen production, and reduces the impact of the electrolyte on both sides of the composite membrane on the ion transport performance of the porous layer.

[0036] In some embodiments, the thickness of the porous layer is 5-30 μm, for example, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 23 μm, 26 μm, 28 μm, or 30 μm. This configuration helps to provide sufficient ion transport and improve ion transport efficiency. At least one of the two dense layers has a thickness greater than 15 μm, for example, 16 μm, 18 μm, 20 μm, 25 μm, or 30 μm. This configuration, when applied in an electrolyzer or battery, forms an effective barrier between the two electrodes.

[0037] In some embodiments, the thickness of the composite membrane is 30~200μm, for example, it can be 30μm, 50μm, 80μm, 100μm, 120μm, 140μm, 160μm, 180μm or 200μm, etc. The composite membrane of this application can meet the membrane thickness requirements of related technologies (in some cases it can be made thinner) while preparing a three-layer membrane, and at the same time achieve that the three layers of the composite membrane do not separate from each other, ensuring the stability of the composite membrane. While improving the various performances of the composite membrane, it further extends the service life of the composite membrane.

[0038] In some embodiments, both the first and second functional groups are positively charged, enabling the composite membrane to act as an anion exchange membrane for OH-. - This will facilitate its subsequent application in fields such as hydrogen production through water electrolysis.

[0039] From the perspective of structural consistency and compatibility, the first functional group and the second functional group are the same. This setting helps to further reduce the occurrence of delamination in the composite membrane and improve the service life of the composite membrane.

[0040] In some embodiments, the composite membrane is an anion exchange membrane, and the first functional group and / or the second functional group are selected from quaternary ammonium salt functional groups or quaternary phosphonium salt functional groups, respectively. This configuration helps to maintain good chemical stability of the composite membrane (e.g., adaptable to a wide pH range) while effectively transporting anions within the composite membrane and improving the overall ion conduction efficiency.

[0041] Furthermore, the first functional group and / or the second functional group are selected from any one of trimethyl quaternary ammonium salts, quaternary phosphonium salts, piperidinium salts, imidazole salts, morpholine salts, quinine salts, pyridine salts, tetrahydropyrrole salts, quinoline salts, indole salts, and spirocyclic quaternary ammonium salts.

[0042] In some embodiments, the composite membrane is a cation exchange membrane, and the first functional group and / or the second functional group are sulfonic acid functional groups. Sulfonic acid functional groups have strong acidity and ionization ability, and can dissociate into a relatively large number of hydrogen ions under humid conditions, thereby effectively promoting the transport of cations (such as sodium ions, potassium ions or hydrogen ions, etc.) and improving the cation conductivity.

[0043] Furthermore, the first functional group and / or the second functional group are sulfonic acid groups, respectively.

[0044] From the perspective of improving mechanical strength, thermal stability and ionic conductivity, the first polymer and / or the second polymer are selected from at least one of polyethylene, polypropylene, styrene-ethylene-butene-styrene block copolymer, polytetrafluoroethylene, polyvinylidene fluoride, polyaryletherketone, polyarylethersulfone, polyimide, polybenzimidazole, polyphenylene, polynorbornene, polyphenylene ether, polyphenylene sulfide, polyarylpiperidine and copolymers or mixtures thereof.

[0045] It should be noted that, based on the ease of obtaining the aforementioned materials and the fact that they do not involve fluorine-containing groups, the cost can be reduced compared to polytetrafluoroethylene membranes in related technologies.

[0046] In some embodiments, the first polymer is a cross-linked polymer. This configuration makes the porous layer easier to form and less prone to miscibility with the casting solution of the dense layer. Furthermore, when the first polymer forms the casting solution, its drying and gel formation promotes adhesion to the dense layer, further preventing delamination between the porous and dense layers. The second polymer can be a cross-linked or non-cross-linked polymer.

[0047] Optionally, the second polymer is a non-crosslinked polymer. This configuration improves the controllability of the viscosity of the second polymer after it forms a gel during subsequent preparation, thereby further reducing the possibility of delamination between the porous layer and the dense layer.

[0048] According to another embodiment of this application, a method for preparing the composite separator as described above is provided. Figure 2 A flowchart illustrating the preparation method of the composite separator according to an embodiment of this application is shown, as follows: Figure 2 As shown, the method includes operations S201 to S204.

[0049] In operation S201, the first casting liquid is coated onto the first substrate to form pores, thereby obtaining a porous base film.

[0050] In operation S201, pores can be formed through phase inversion. Phase inversion is a method of preparing a porous base membrane into a porous layer, such as solvent-induced phase separation, vapor-induced phase separation, template method, or plasma method. Solvent-induced phase separation can be understood as using a non-solvent to induce phase inversion. When a liquid containing a non-solvent comes into contact with the porous base membrane, the non-solvent diffuses into the porous base membrane. At this time, the solvent soluble in the non-solvent in the porous base membrane dissolves from the coating, causing the first polymer insoluble in the non-solvent to solidify and form a porous layer. Vapor-induced phase separation can be understood as evaporating the solvent in the first casting solution under certain temperature and humidity conditions. As the solvent decreases, the first casting solution undergoes phase separation and eventually solidifies into a porous base membrane. Template method can be understood as depositing the first casting solution onto a template, with deposition methods including dip coating, spin coating, electrochemical deposition, etc., and then removing the template, for example, by calcination or chemical dissolution, to obtain a porous layer. Different process gases, such as oxygen, argon, and nitrogen, can be introduced into the plasma. Through the interaction between the plasma and the porous base film, tiny pits or voids are formed, thus obtaining a porous layer.

[0051] It should be noted that "non-solvent" can be understood as having the property of substantially not dissolving the first polymer, allowing the porous membrane to be immersed in a liquid containing the non-solvent. "Substantially not dissolving the first polymer" means that the solubility of the first polymer relative to 100g of solvent is less than 100mg at 25°C. The non-solvent can be pure water, distilled water, ion-exchanged water, etc.; lower alcohols such as methanol, ethanol, propanol, etc.; or mixtures thereof. From the perspective of facilitating post-processing, water is preferred, and ion-exchanged water is more preferred.

[0052] The method for coating the first casting liquid onto the first substrate can be die coating, spin coating, gravure coating, spray coating, or using a coating machine. The first substrate is a film or sheet, glass plate, etc., made of resins such as polybutylene terephthalate, polyethylene naphthalate, polypropylene, polyethylene, polyvinyl chloride, polyvinyl alcohol acetal, polymethyl methacrylate, and polycarbonate.

[0053] In operation S202, the second casting liquid is applied to the second substrate and partially dried to obtain an adhesive coating.

[0054] In this operation S202, partial drying helps remove most of the solvent from the second casting solution, preparing it into a viscous coating that facilitates subsequent tight bonding with the porous base membrane. The method for coating the second casting solution onto the second substrate and the selection of the second substrate are the same as described above and will not be repeated here.

[0055] It should be noted that the first substrate and / or the second substrate may also include a support as needed, but since this is not the focus of this application, it will not be elaborated here.

[0056] In operation S203, a porous base film is coated onto an adhesive coating and dried to obtain a porous layer with a uniform dense layer on the surface.

[0057] In this operation S203, due to permeation, the pores on the surface of the porous base membrane are filled with a viscous coating, followed by drying, resulting in a tight bond between the dense layer and the porous layer. The first casting solution is a first polymer solution with a first functional group; the second casting solution is a second polymer solution with a second functional group; the first polymer and the second polymer have the same main chain, and because they have the same main chain, there is no obvious phase interface or phase boundary at their interface.

[0058] In operation S204, the surface of a porous layer with a uniform dense layer away from the dense layer is covered with another adhesive coating and dried to obtain a composite membrane.

[0059] In this operation S204, similar to S203, a viscous coating fills the pores on the surface of the porous layer away from the dense layer, making the three-layer structure of the composite membrane more tightly bonded.

[0060] According to the embodiments of this application, the first functional group and the second functional group are ionic groups with the same polarity; based on the same main chain of the first polymer and the second polymer, the three-layer structure of the composite membrane is more tightly integrated, which in turn makes the three-layer structure more compatible. There is no obvious phase interface between the porous layer and each dense layer, so that the composite membrane has better integrity and consistency.

[0061] In addition to the above operations, known processes such as pressing can be performed as needed to make the density of the composite diaphragm more uniform.

[0062] The following section will detail the entire process of composite membrane preparation using solvent-induced phase separation pore formation.

[0063] Figure 3 The following diagram illustrates the fabrication process of a composite membrane according to an embodiment of this application. Figure 3 As shown, the first casting solution is scraped onto a coating plate and placed in an oven for pre-evaporation. The purpose of pre-evaporation is to remove most of the solvent from the first casting solution to facilitate subsequent pore formation. The coagulation bath can be understood as a method of contacting a porous base film with a liquid containing a non-solvent, and further, a method of immersing the coating film in a liquid containing a non-solvent.

[0064] There is no temperature limit for the non-solvent-containing liquid when in contact with the porous membrane. For the purpose of facilitating uniform solidification of the porous membrane, the temperature can be 10-50℃. There is no time limit for immersing the porous membrane in the non-solvent-containing liquid. The porosity, pore structure, and pore size of the porous layer can be controlled by controlling the process conditions of the solidification bath.

[0065] The second casting solution is scraped onto a coating plate and placed in an oven for pre-evaporation. The purpose of pre-evaporation is to remove most of the solvent in the second casting solution to form a viscous coating, which facilitates the subsequent application of a porous base film onto the surface of the viscous coating, ensuring that there is no obvious phase interface between the porous layer and the dense layer.

[0066] like Figure 3 As shown in the rectangular frame, due to the permeation effect, the micropores on the surface of the porous base membrane are filled by the undried adhesive coating, making the three-layer composite membrane more tightly bonded.

[0067] In some embodiments, the first casting solution is prepared by mixing a first polymer having a first group with a crosslinking agent in an organic solution. The mixing method can be conventional, such as mechanical stirring, to allow the first group to react with the crosslinking agent, thus obtaining the first casting solution. Multiple first polymers are chemically bonded together using the crosslinking agent to construct a crosslinked first polymer. Preparing the first polymer as a crosslinked polymer helps avoid miscibility between the porous base membrane and the adhesive coating when they come into contact during preparation. This ensures the formation of a stable porous layer structure during preparation, improves the mechanical strength of the porous layer, and enhances its thermal and chemical stability.

[0068] From the perspective of improving the solubility and mixing uniformity of the first polymer and / or the second polymer, the organic solvent may be selected from at least one of dimethyl sulfoxide and tetrahydrofuran.

[0069] In some embodiments, when the composite membrane is an anion exchange membrane, the first group includes an amino group, a halogen group, an alkenyl group, or an alkynyl group, wherein there is at least one alkenyl or alkynyl group in the first group; when the first group includes an amino group or a halogen group, a cross-linked first polymer is formed through the mutual reaction between the amino group and the halogen group; when the first group includes an alkenyl or alkynyl group, the cross-linking agent contains at least two groups that can react with the alkenyl or alkynyl group, such as at least two alkenyl groups, at least two alkynyl groups, at least two mercapto groups, at least two epoxy groups, at least two silane groups, etc., specifically C2~C groups having at least two unsaturated double bonds. 10 Olefins.

[0070] Specifically, when the first group is an amino group, the crosslinking agent is a polyhalogenated hydrocarbon, wherein the halogen in the polyhalogenated hydrocarbon can be chlorine or bromine, and the number of halogens in the polyhalogenated hydrocarbon can be 2 to 12, for example, 2, 4, 6, 8, 10, or 12; the amino group can be a primary amino group, a secondary amino group, or a tertiary amino group. For example, the reaction process of the tertiary amino group crosslinking with the dihalogenated hydrocarbon is shown in the following formula (I).

[0071] Formula (I), where X is Cl or Br, and m is 2~12.

[0072] Alternatively, when the first group is a halogen, the crosslinking agent is a polyamine. The halogen can be chlorine or bromine, and the polyamine can have 2, 3, or 4 amino groups. When the polyamine is a diamine, the number of carbon atoms bonded between the two amino groups can be 1 to 6, specifically piperazine, 1,4-diazahexacyclic, heptane, ethylenediamine, 1,2-dimethylethylenediamine, 1,3-diaminopropane, putrescine, cadaverine, hexamethylenediamine, diphenylethylenediamine, 1,4-diazaheptane, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, p-phenylenediamine, m-phenylenediamine, o-phenylenediamine, and combinations thereof. For example, the crosslinking reaction of a halogen with a diamine is shown in equation (II) below.

[0073] Formula (II), where Y is Cl or Br, and n is 1 to 6.

[0074] Alternatively, the first group may include C2~C 10 Alkenyl group, wherein the first group has at least one unsaturated double bond; in this case, the crosslinking agent can be a C2~C group having at least two unsaturated double bonds. 10 Olefins. For example, the two-step reaction process, involving the sequential addition polymerization and quaternization reaction via a first group and a crosslinking agent, can be represented by the following equation (III):

[0075] Formula (III), where Z is Cl or Br, and R is a group in the crosslinking agent that is attached to an amine group.

[0076] When the composite membrane is a cation exchange membrane, the first group may include C2~C3. 10 Alkenyl or alkynyl, wherein the first group contains at least one unsaturated double or triple bond; in this case, the crosslinking agent can be a C2~C group having at least two unsaturated double bonds. 10 Olefins. For example, the reaction process of addition polymerization via a first group and a crosslinking agent can be shown as follows (IV):

[0077] Formula (IV).

[0078] In some embodiments, when the composite membrane is an anion exchange membrane, the preparation method further includes: before S202, quaternizing or quaternizing the second group of the second polymer to obtain a second polymer having a second functional group; or, after S204, quaternizing or quaternizing the second group of the second polymer in the composite membrane to obtain a second polymer having a second functional group.

[0079] It should be noted that quaternization or quaternization can be performed during the preparation of the coating or after the composite coating has been formed. Through the above-mentioned quaternization or quaternization, the functional groups in the porous layer and the dense layer of the composite membrane are kept consistent and both carry a positive charge. When subsequently applied to anion exchange membranes, this can promote the transport of anions, improve ion conduction efficiency, and further reduce membrane delamination.

[0080] In some embodiments, the number of the first functional group differs from the number of the second functional group. The ion exchange capacity is adjusted by varying the content of both functional groups. Ion exchange capacity (IEC) can be understood as the amount of ions that a unit volume or unit mass of ion exchange material can exchange. The unit of IEC can be meq / g under dry conditions or meq / mL under wet conditions. IEC reflects the interaction between the functional groups and the target ion (e.g., OH-). - or H + This design allows for the adjustment of the water absorption rates of the porous and dense layers to be similar, thereby preventing water accumulation in the porous layer. It is understood that the composite membrane prepared in this application possesses good ion conductivity and gas barrier properties, while also exhibiting high mechanical strength. When applied to alkaline water electrolysis for hydrogen production, it demonstrates alkali resistance and resistance to high and low temperatures, improving the safety and stability of hydrogen production in alkaline water electrolysis.

[0081] According to another embodiment of this application, a composite membrane as described above is provided for use in alkaline water electrolysis for hydrogen production, fuel cells, flow batteries, and seawater desalination.

[0082] It is understandable that the aforementioned composite membrane can be used as an anion exchange membrane in alkaline water electrolysis for hydrogen production, fuel cells, and flow batteries; and as a cation exchange membrane in seawater desalination.

[0083] When applied to alkaline water electrolysis for hydrogen production, it can effectively conduct OH-. - Ions improve the stability and service life of composite membranes.

[0084] When applied to fuel cells, it can provide excellent anion conduction capabilities, promoting electrode reactions. Compared to traditional proton exchange membrane fuel cells, the composite membrane of this application may use cheaper materials when applied to the fuel cell field, thereby reducing costs.

[0085] When applied to flow batteries, it helps to improve the selective passage of target ions. Because flow batteries operate in harsh environments, the composite separator of this application exhibits good stability and corrosion resistance, enabling long-term use and improving the reliability and lifespan of the flow battery.

[0086] When applied to seawater desalination, it can effectively conduct cations and achieve efficient desalination. Furthermore, the surface of the cation exchange membrane in this application is relatively smooth, which reduces the risk of biological contamination and structural damage. Due to the stability of the multilayer structure, its durability and reliability in the seawater environment are improved.

[0087] In some implementations, the composite membrane is used as an alkaline anion exchange membrane in alkaline water electrolysis for hydrogen production.

[0088] In alkaline water electrolysis for hydrogen production, composite membranes, acting as alkaline anion exchange membranes, can effectively conduct OH-. - Ions enhance the compactness of the composite membrane, which helps improve electrolysis efficiency. Furthermore, under the long-term impact of electrolyte and generated gas, they reduce membrane delamination, thereby improving the stability and service life of the composite membrane.

[0089] The present application is further illustrated below through embodiments, accompanying drawings, and related test experiments and results. In the following detailed description, numerous specific details are set forth for ease of explanation to provide a comprehensive understanding of the embodiments of the present application. However, it is apparent that one or more embodiments may be implemented without these specific details. Moreover, the details in the following embodiments can be arbitrarily combined to form other feasible embodiments without conflict.

[0090] It should be noted that the specific embodiments described below are merely illustrative examples, and the scope of protection of this application is not limited thereto. The chemicals and raw materials used in the following embodiments are all commercially available or prepared using recognized processing methods.

[0091] It should be noted that the ionic conductivity, porosity, and ion exchange capacity of the composite membrane were all tested using national standard testing methods. Ion conductivity was tested using an AC impedance meter (model 1287 or 1260) to measure the impedance of the composite membrane, with a frequency range of 1~10. 6The ion conductivity was calculated based on the ionic resistance obtained from the test at Hz and a test temperature of 25℃. Porosity was tested using mercury porosimetry, measuring the amount of mercury adsorbed by the composite membrane and calculating its porosity. Ion exchange capacity was tested as follows: A membrane sample with a mass of at least 0.5 g was dried in an oven to constant weight, and the mass was recorded as m (in g). The membrane sample was cut into small pieces and soaked in 200 mL of 1M sodium chloride solution for 24 h. The sample was then rinsed with deionized water and soaked in 200 mL of 1M sodium nitrate solution for 24 h. The chloride ion content in the soaked sodium nitrate solution was titrated with silver nitrate standard solution and recorded as M (in mmol). The IEC of the membrane sample was calculated using the following formula: IEC = M / m (in mmol / g).

[0092] Example 1:

[0093] 1g of chloromethylated styrene-ethylene-butene-styrene block copolymer (SEBS) was dissolved in 20mL of tetrahydrofuran, and 0.3mL of tetramethylethylenediamine was added. After stirring and reacting, the mixture was uniformly coated onto a clean glass plate. The glass plate was placed in a constant temperature and humidity chamber and dried at 25℃ and 80~90% humidity for 24h. A porous structure was prepared by vapor-induced phase separation. The film thickness was controlled to be about 20μm by coating to obtain a cross-linked porous base membrane.

[0094] Dissolve 1g of chloromethylated SEBS in 20mL of tetrahydrofuran and coat it evenly on a clean glass plate. Control the film thickness to about 25μm by coating. Place the glass plate in a 25℃ oven and dry it until it is sufficiently viscous. Then, coat the surface with the obtained cross-linked porous base film and continue to dry until completely dry to obtain a porous layer covered with a dense layer.

[0095] 1g of chloromethylated SEBS was dissolved in 20mL of tetrahydrofuran and evenly coated onto a clean glass plate. The film thickness was controlled to be around 25μm by the coating thickness. The glass plate was placed in an oven at 25℃ and dried until it was sufficiently viscous. Then, a porous layer covered with a dense layer was applied to its surface, with the porous side in contact with the viscous solution in the lower layer. The plate was dried until completely dry to obtain the composite preform.

[0096] The composite pre-fabricated membrane was soaked in a 5% trimethylamine aqueous solution for 48 hours (to convert all chloromethyl groups into quaternary ammonium ions), then washed three times with deionized water and soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 hours. After being washed three times with deionized water, the sandwich-structured anion exchange membrane 1 was obtained.

[0097] Comparative Example 1-1:

[0098] 1 g of chloromethylated SEBS was dissolved in 20 mL of tetrahydrofuran and evenly coated onto a clean glass plate. The film thickness was controlled to be around 70 μm by coating. The glass plate was placed in an oven at 25 °C and dried completely. Then, it was soaked in a 5% trimethylamine aqueous solution for 48 h to quaternize. After being removed and washed three times with deionized water, it was soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After being removed and washed three times with deionized water, a dense anion exchange membrane 1'-1 was obtained.

[0099] Comparative Examples 1-2:

[0100] 1 g of chloromethylated SEBS was dissolved in 20 mL of tetrahydrofuran, and 0.3 mL of tetramethylethylenediamine was added. After stirring and reacting, the mixture was evenly coated onto a clean glass plate. The glass plate was placed in a constant temperature and humidity chamber and dried at 25 °C for 24 h. The film thickness was controlled to be around 20 μm by coating to obtain a cross-linked dense film with a porosity of 0.

[0101] Dissolve 1g of chloromethylated SEBS in 20mL of tetrahydrofuran and coat it evenly on a clean glass plate. Control the film thickness to about 25μm by coating. Place the glass plate in a 25℃ oven and dry it until it is sufficiently viscous. Then, coat the surface of the obtained cross-linked dense film and continue to dry until completely dry to obtain a two-layer composite film.

[0102] 1 g of chloromethylated SEBS was dissolved in 20 mL of tetrahydrofuran and evenly coated onto a clean glass plate. The film thickness was controlled to be around 25 μm by coating. The glass plate was placed in a 25 °C oven and dried until sufficiently viscous. The two-layer composite film was then applied to its surface and dried further until completely dry. Subsequently, it was soaked in a 5% trimethylamine aqueous solution for 48 h, washed three times with deionized water, and then soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After that, it was washed three times with deionized water to obtain a dense anion exchange membrane 1'-2.

[0103] Example 2:

[0104] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.2 mL of 1,6-dibromohexane was added. The 1,6-dibromohexane reacted with piperidine, functionalizing it from a tertiary amine to a quaternary ammonium group, simultaneously forming a cross-linked polymer. After stirring at room temperature, the mixture was uniformly coated onto a clean glass plate, with the film thickness controlled to approximately 20 μm. The glass plate was placed in an oven and pre-evaporated at 80 °C for 1 h, then immersed in a coagulation bath composed of ethanol and deionized water (volume ratio 1:1). Pores were formed by utilizing the difference in solubility of the cross-linked polymer and dimethyl sulfoxide in the mixed solution of ethanol and deionized water. The membrane was removed, washed, and dried to obtain a cross-linked porous base membrane. The cross-linking and quaternization process is shown in the following formula, where 'a' represents the number of repeating units of poly(p-terphenylpiperidine).

[0105]

[0106] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.3 mL of iodomethane was added and stirred for 8 h to carry out a quaternization reaction. The resulting solution was then uniformly coated onto a clean glass plate, with the film thickness controlled to approximately 25 μm. The glass plate was then dried in an 80 °C oven until sufficiently viscous. The resulting cross-linked porous base film was then applied to the surface, and the plate was dried further until completely dry, resulting in a porous layer covered with a dense layer. The quaternization process is shown in the following formula.

[0107]

[0108] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.3 mL of iodomethane was added. After stirring for 8 h, the mixture was evenly coated onto a clean glass plate. The film thickness was controlled to be about 25 μm by the coating thickness. The glass plate was placed in an 80 °C oven and dried until sufficiently viscous. The surface of the porous layer covered with the dense layer was then placed on the surface layer, with the porous side in contact with the viscous solution. The plate was dried until completely dry. Then, it was soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After removal, it was washed three times with deionized water to obtain the sandwich-structured anion exchange membrane 2.

[0109] Furthermore, the counterion is exchanged from the halogen to OH. - The process is shown in the following formula.

[0110]

[0111] For the composite membrane of Example 2, scanning electron microscopy clearly shows that the three membrane layers are tightly bonded and there is no obvious phase interface. The thickness of the porous layer with microporous structure is measured to be 8~10μm. The thickness of the porous layer in the composite membrane is less than the thickness of the cross-linked porous base membrane prepared in the first step. The reason is that during the preparation process, when the surface of the cross-linked porous base membrane comes into contact with the coating liquid on both sides, some of the solution seeps into the micropores of the porous layer and fills part of the micropores.

[0112] Comparative Example 2-1:

[0113] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.3 mL of iodomethane was added. After stirring for 8 h, the mixture was evenly coated onto a clean glass plate. The film thickness was controlled to be around 70 μm by adjusting the coating thickness. The glass plate was dried in an 80 °C oven until completely dry, and then soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After removal, the membrane was washed three times with deionized water to obtain a dense anion exchange membrane 2'-1.

[0114] Comparative Example 2-2:

[0115] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.2 mL of 1,6-dibromohexane was added. After stirring at room temperature for 0.5 h, the mixture was uniformly coated onto a clean glass plate. The film thickness was controlled to be around 20 μm by adjusting the coating thickness. The glass plate was placed in an oven and pre-evaporated at 80 °C for a certain period of time. Then, it was immersed in a coagulation bath composed of ethanol and deionized water. The film was removed, cleaned, and dried to obtain a cross-linked dense film with a porosity of 0.

[0116] Dissolve 1g of poly(p-terphenylpiperidine) in 10mL of dimethyl sulfoxide, add 0.3mL of iodomethane and stir for 8h. Then, coat the mixture evenly onto a clean glass plate. Control the film thickness to about 25μm by coating thickness. Place the glass plate in an 80℃ oven and dry it until it is sufficiently viscous. Then, coat the surface with the obtained cross-linked dense film and continue drying until completely dry to obtain a two-layer composite film.

[0117] 1 g of poly(p-terphenylpiperidine) was dissolved in 10 mL of dimethyl sulfoxide, and 0.3 mL of iodomethane was added. After stirring for 8 h, the mixture was evenly coated onto a clean glass plate. The film thickness was controlled to be around 25 μm by adjusting the coating thickness. The glass plate was placed in an 80 °C oven and dried until sufficiently viscous. Then, the two composite membranes were applied to the surface and dried until completely dry. Subsequently, the membrane was soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After removal, the membrane was washed three times with deionized water to obtain a dense anion exchange membrane 2'-2.

[0118] Example 3:

[0119] Preparation of chloromethylated polyether ether ketone (CMPEEK): At -10℃, 1g of polyether ether ketone was dissolved in 60mL of concentrated sulfuric acid and stirred for 2 hours until completely dissolved. 20mL of chloromethyl octyl ether was added, and the mixture was stirred until the reaction was complete. The solution was then poured into 600mL of deionized water, causing a precipitate to form. The precipitate was filtered, washed repeatedly with deionized water until neutral, and dried under vacuum at 30℃ to constant weight to obtain CMPEEK. The chloromethylation process of polyether ether ketone is shown in the following formula, where b represents the number of repeating units.

[0120]

[0121] 1 g of CMPEEK was dissolved in 20 mL of N,N-dimethylformamide, and 0.3 mL of tetramethylethylenediamine was added. After stirring and reacting, the mixture was uniformly coated onto a clean glass plate. The glass plate was then placed in a constant temperature and humidity chamber and dried at 60℃ and 80-90% humidity for 24 h. A porous structure was prepared by vapor-induced phase separation. The film thickness was controlled to be around 20 μm by coating, resulting in a cross-linked porous base membrane. The cross-linking and quaternization processes are shown in the following formula.

[0122]

[0123] 1 g of CMPEEK was dissolved in 20 mL of N,N-dimethylformamide, and 0.25 mL of 1-methylimidazole was added. After stirring and reacting, the mixture was uniformly coated onto a clean glass plate. The reaction process is shown in the following formula. The film thickness was controlled to be around 25 μm by coating. The glass plate was placed in a 60 °C oven and dried until sufficiently viscous. The resulting cross-linked porous base film was then coated onto the surface, and the plate was dried further until completely dry, resulting in a porous layer covered with a dense layer.

[0124]

[0125] Dissolve 1g of CMPEEK in 20mL of N,N-dimethylformamide and coat it evenly on a clean glass plate. Control the film thickness to about 25μm by coating thickness. Place the glass plate in a 60℃ oven to dry until sufficiently viscous. Then cover the surface of the plate with a porous layer covered with a dense layer, with the porous side in contact with the viscous solution in the lower layer. Continue drying until completely dry. Then soak in 5% N-methylpiperidine aqueous solution for 48h (to convert the remaining chloromethyl group into piperidinium salt), as shown in the following formula.

[0126]

[0127] After being removed and washed three times with deionized water, the membrane was soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 hours. After being removed and washed three times with deionized water, the sandwich-structured anion exchange membrane 3 was obtained.

[0128] Comparative Example 3:

[0129] The preparation method of CMPEEK is the same as in Example 3.

[0130] 1 g of CMPEEK was dissolved in 20 mL of N,N-dimethylformamide, and 0.3 mL of tetramethylethylenediamine was added. After stirring and reacting, the mixture was evenly coated onto a clean glass plate. The glass plate was dried at 60 °C for 24 h to obtain a cross-linked dense membrane with a porosity of 0.

[0131] Dissolve 1g of CMPEEK in 20mL of N,N-dimethylformamide, add 0.25mL of 1-methylimidazole, stir and react, then coat evenly onto a clean glass plate. Control the film thickness to about 25μm by coating. Place the glass plate in a 60℃ oven and dry until sufficiently viscous. Then, coat the surface with the obtained cross-linked dense film and continue drying until completely dry to obtain a two-layer composite film.

[0132] 1 g of CMPEEK was dissolved in 20 mL of N,N-dimethylformamide and uniformly coated onto a clean glass plate. The film thickness was controlled to be around 25 μm by the coating thickness. The glass plate was placed in a 60 °C oven and dried until sufficiently viscous. A porous layer covered with a dense layer was then placed on its surface, followed by the two-layer composite membrane. The membrane was dried further until completely dry. Then, it was soaked in a 5% trimethylamine aqueous solution for 48 h. After being removed and washed three times with deionized water, it was soaked in a 1 mol / L potassium hydroxide aqueous solution for 24 h. After being removed and washed three times with deionized water, a dense anion exchange membrane was obtained.

[0133] Example 4:

[0134] Copolymer 1 and copolymer 2 were synthesized according to the method in Chinese Patent CN118852623A, as shown in the following formula, where d represents the number of repeating units in copolymer 1 and e represents the number of repeating units in copolymer 2.

[0135]

[0136]

[0137] 1g of copolymer 1 was dissolved in 10mL of dimethyl sulfoxide and uniformly coated onto a clean glass plate. The film thickness was controlled to be around 20μm by coating. After pre-evaporation in an oven, the glass plate was immersed in water to form pores. The film was then removed, cleaned, and dried to obtain a porous membrane. The porous membrane was placed in a high-temperature oven and heat-treated at 300℃ for 2 hours to induce self-crosslinking. After the temperature was reduced to room temperature, a crosslinked porous base membrane was obtained.

[0138] 1g of copolymer 2 was dissolved in 10mL of dimethyl sulfoxide and uniformly coated on a clean glass plate. The film thickness was controlled to be about 25μm by coating thickness. The glass plate was placed in an oven and dried until it was sufficiently viscous. The obtained cross-linked porous base film was then coated on the surface and dried until completely dry to obtain a porous layer covered with a dense layer.

[0139] 1 g of copolymer 2 was dissolved in 10 mL of toluene and uniformly coated onto a clean glass plate. The film thickness was controlled to be approximately 25 μm by adjusting the coating thickness. The glass plate was dried in an oven until sufficiently viscous. The surface of the porous layer, which was previously covered with a dense layer, was then coated onto the surface of the plate, with the porous side in contact with the viscous solution. The plate was dried further until completely dry to obtain the composite pre-film. The composite pre-film was then acidified in 1 mol / L dilute hydrochloric acid for 24 h to obtain a sandwich-structured cation exchange membrane.

[0140] Examples 1 to 4 and Comparative Examples 1-1 to 2-2 and Comparative Example 3 were tested, and the test results are shown in Table 1 below.

[0141] Table 1. Membrane performance of the examples and comparative examples

[0142]

[0143] Comparing Example 1 with Comparative Examples 1-1 and 1-2, it can be seen that, with similar ion exchange capacities, the composite membrane prepared in Example 1, with two dense layers sandwiching a porous layer, exhibits higher ion conductivity. Similarly, comparing Example 2 with Comparative Examples 2-1 and 2-2, it can be seen that, with similar ion exchange capacities, the composite membrane prepared in Example 2, with two dense layers sandwiching a porous layer, exhibits higher ion conductivity. Although the functional groups of the dense layer and the porous layer of the anion exchange membrane 3 prepared in Example 3 are different, it still exhibits good ion conductivity. In contrast, Comparative Example 3, due to the fact that the porosity of its several layers is all 0, has poorer ion conductivity compared to Example 3. The cation exchange membrane prepared in Example 4 also exhibits high ion conductivity, which is beneficial for subsequent applications in fields such as seawater desalination. The above demonstrates that the sandwich structure of the composite membrane with the same main chain of this application can achieve high ion conductivity while also having good gas barrier effect due to the consistency of the structure, and can be widely used in the field of anion exchange membrane adaptation for a long time.

[0144] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of this application. It should be understood that the above descriptions are merely specific embodiments of this application and are not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A composite membrane comprising a porous layer and two dense layers, the two dense layers being located on opposite surfaces of the porous layer; The porous layer is made of a first polymer having a first functional group, and the dense layer is made of a second polymer having a second functional group; the first polymer and the second polymer have the same main chain; the first functional group and the second functional group are ionic groups with the same polarity.

2. The composite diaphragm according to claim 1, wherein, The porous layer has multiple pore structures, at least some of which are independent of each other.

3. The composite diaphragm according to claim 1 or 2, wherein, The porosity of the porous layer is 5-23%, preferably 8-12%.

4. The composite diaphragm according to claim 2, wherein, The pore structure has a dimension of 0.1~0.8μm in the length direction of the porous layer and a dimension of 0.1~0.8μm in the width direction of the porous layer; Preferably, the pore structure has a dimension of 0.4~0.6μm in the length direction of the porous layer and a dimension of 0.4~0.6μm in the width direction of the porous layer.

5. The composite diaphragm according to claim 1 or 2, wherein, The porosity of the dense layer is less than 3%, and the porosity of at least one of the two dense layers is 0.

6. The composite diaphragm according to claim 1 or 2, wherein, The thickness of the porous layer is 5-30 μm, and the thickness of at least one of the two dense layers is greater than 15 μm.

7. The composite diaphragm according to claim 1 or 2, wherein, The thickness of the composite diaphragm is 30~200μm.

8. The composite diaphragm according to claim 1 or 2, wherein, Both the first functional group and the second functional group are positively charged, and preferably the first functional group and the second functional group are the same.

9. The composite diaphragm according to claim 1 or 2, wherein, The composite membrane is an anion exchange membrane, and the first functional group and / or the second functional group are respectively selected from quaternary ammonium salt functional groups or quaternary phosphorus salt functional groups; Preferably, the first functional group and / or the second functional group are selected from any one of trimethyl quaternary ammonium salt, quaternary phosphonium salt, piperidinium salt, imidazole salt, morpholine salt, quinine salt, pyridine salt, tetrahydropyrrole salt, quinoline salt, indole salt, and spirocyclic quaternary ammonium salt.

10. The composite diaphragm according to claim 1, wherein, The first polymer and / or the second polymer are selected from at least one of polyethylene, polypropylene, styrene-ethylene-butene-styrene block copolymer, polytetrafluoroethylene, polyvinylidene fluoride, polyaryletherketone, polyarylethersulfone, polyimide, polybenzimidazole, polyphenylene, polynorbornene, polyphenylene ether, polyphenylene sulfide, polyarylpiperidine, and copolymers or mixtures thereof.

11. The composite diaphragm according to claim 1 or 2, wherein, The first polymer is a cross-linked polymer; The second polymer is a cross-linked polymer or a non-cross-linked polymer.

12. The composite diaphragm according to claim 1 or 2, wherein, The composite membrane is a cation exchange membrane, and the first functional group and / or the second functional group are sulfonic acid functional groups, respectively.

13. A method for preparing a composite diaphragm, comprising: The first casting solution is coated onto the first substrate to form pores, thereby obtaining a porous base film. The second casting solution is applied to the second substrate and partially dried to obtain an viscous coating. The porous base film is covered on the adhesive coating and dried to obtain a porous layer with a uniform dense layer on the surface; The surface of the porous layer with a uniform dense layer away from the dense layer is covered with another adhesive coating film and then dried to obtain a composite membrane. Wherein, the first casting solution is a first polymer solution having a first functional group; the second casting solution is a second polymer solution having a second functional group; the first polymer and the second polymer have the same main chain; the first functional group and the second functional group are ionic groups with the same polarity.

14. The preparation method according to claim 13, wherein, The first casting solution is prepared by the following method: A first polymer having a first group is mixed with a crosslinking agent in an organic solution, such that the first group reacts with the crosslinking agent to obtain the first casting solution.

15. The preparation method according to claim 13, wherein, The first group includes an amino group, a halogen group, an alkenyl group, or an alkynyl group; When the first group is an amino group, the crosslinking agent is a polyhalogenated hydrocarbon; When the first group is a halogen, the crosslinking agent is a polyamine; When the first group is an alkenyl or alkynyl group, the crosslinking agent contains at least two alkenyl groups, at least two alkynyl groups, at least two mercapto groups, at least two epoxy groups, or at least two silane groups.

16. The preparation method according to claim 13, wherein, The preparation method further includes: Before partially drying the second casting solution applied to the second substrate, the second functional group of the second polymer is quaternized or quaternized to obtain a second polymer with the second functional group; or, After coating the surface of the porous layer covered with a uniform dense layer, away from the dense layer, onto another adhesive coating film and drying it, The second polymer in the composite membrane is quaternized or quaternized to obtain a second polymer with a second functional group.

17. The preparation method according to claim 13, wherein, The number of the first functional group is different from the number of the second functional group.

18. The application of a composite membrane as described in any one of claims 1 to 12 in alkaline water electrolysis for hydrogen production, fuel cells, flow batteries, and seawater desalination.

19. The application according to claim 18, wherein, The composite membrane is used as an alkaline anion exchange membrane in alkaline water electrolysis for hydrogen production.

Citation Information

Patent Citations

  • Sulfonated polyimide containing alkynyl, preparation method and method for preparing cross-linked proton exchange membrane by using sulfonated polyimide containing alkynyl

    CN118852623A